Desenvolvimento de procedimento automático para determinação fotométrica de N-ureídos totais em leguminosas empregando multicomutação em fluxo - Kamogawa, Carla Cripa Crispino (Universidade Federal de São Carlos, 2007)
This work aimend the development of an automated procedure for photometric determination of total ureide in soybean tissues using multicommutation in flow analysis. The photometric detection was based on the formation of indophenol blue (the Berthelot reaction), which involving oxidation of the amide nitrogen (N-ureide) by hypochlorite and reaction with phenol in alkaline medium. The manifold hardware and the instrument for photometric detection using a LED as radiation source and a photodiode as detector were developed. The system was microcomputer by a software written in QuickBasic 4.5. In the optimization of the proposed procedure the following parameters were considered: the hypochlorite concentration and its alkalinity, the phenol concentration and its alkalinity, the reaction temperature, the sample residence time, the volume of the phenol solution and the removal of interferences by ion exchange resin column. After optimization, the analytical curve was linear in the 30 to 260 μmol L-1 concentration range with a limit of detection of 1 μmol L-1, a relative standard deviation lower than 3%, consumption of 6.7 mg phenol per determination and sample throughput of 22 determinations per hour. The developed procedure was used for N-ureide determination in soybean leaves extracts. With results was agreement with the reference method at the 95% confidence level. The developed procedure is suitable for routine analysis in laboratories conducting research in Soil Microbiology and Biological Nitrogen Fixation with advantages in relation to precision, operational costs and waste generation.
Development of an automatic procedure for photometric determination of total N-ureide in legume using ulticommutation flow
Keywords: Química; Análise em fluxo; Soja; Espectrofotometria; Nitrogênio fixação; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA